PENINGKATAN PRODUKSI DAN TATA KELOLA BISNIS PADA SENTRA PENGRAJIN KERIS DI DESA AENG TONG TONG SUMENEP-MADURA - Hafidhah Hafidhah; Mohammad Herli; Miftahol Arifin; Auliana Diah Wilujeng (Universitas Mataram, 2023)
The background of the activity is that there is a unique potential in the cultural heritage of the keris which can be used as a local economic asset but needs to be improved in production and marketing. The keris craft in Aeng Tong Tong Village has developed and become the foundation of people's lives. In addition, this keris craft center has become one of the main tourist destinations in Sumenep Regency, so its existence needs to be preserved. This service activity aims to empower keris artisans in Aeng Tong Tong Village, Sumenep – Madura, in production and business management. The activity includes an initial survey to identify constraints and opportunities, technical training in making keris with a mechanical forging machine, and introduction and training on the concept of good business governance. The participatory approach allows artisans to plan production improvements, financial management, and marketing strategies. The results of this activity show a significant increase in the production of keris through mechanical forging, the improvement both in terms of quality and quantity. Increased production is achieved by implementing automated forging machines to achieve sustainable Keris UMKM. Artisans have also been able to apply the modern techniques taught and adopt more efficient business governance principles. This is reflected in increased income and broader market access. This community service activity increased production and business management at the Keris craftsman center in Aeng Tong Tong Village. This charity program has significantly impacted keris artisans in Aeng Tong Tong Village. Increasing production capacity and improving business governance were achieved in this activity. Participatory approaches and training approaches have proven effective in empowering local communities.